1982
DOI: 10.1128/aac.22.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of ketoconazole in patients with neoplastic diseases

Abstract: Twenty-seven patients with advanced malignancies were given 200 mg of ketoconazole orally every 6 or 12 h. Blood samples were collected during these intervals and after the last dose to determine plasma concentrations and half-lives. The mean plasma concentrations measured after the initial dose were 1.7 +/- 1.1 microgram/ml at 2 h, 0.9 +/- 0.2 microgram/ml at 6 h, and 0.7 +/- 0.4 microgram/ml at 8 h. Plasma concentrations rose significantly in patients on the every-6-h schedule. Concentrations were more varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

1983
1983
1990
1990

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…The t1/2 of ketoconazole has shown some variation in single-dose and multiple-dose studies (2,3,5,6,8,13,14). Some of the more extreme values (9) are difficult to explain, even after allowing for the different methods used.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The t1/2 of ketoconazole has shown some variation in single-dose and multiple-dose studies (2,3,5,6,8,13,14). Some of the more extreme values (9) are difficult to explain, even after allowing for the different methods used.…”
Section: Resultsmentioning
confidence: 99%
“…Some of the more extreme values (9) are difficult to explain, even after allowing for the different methods used. Most studies have shown that t1j2 increases with chronic dosing (3,5,13). However, in one study the t112 of ketoconazole in patients with leukemia was found to be less than 1 h (9).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Less than 1% is free in the plasma. The blood half-life, which is dose dependent, ranges from 1 to 11 h (9). After a single oral dose of 200 mg in humans, detectable levels have been found in the cerebrospinal fluid, urine, saliva, cerumen, and sebum (5).…”
mentioning
confidence: 99%
“…Its pharmacokinetics after oral dosing have been examined in normal subjects (Daneshmend et al, 1981(Daneshmend et al, , 1983Gascoigne et al, 1981;Mannisto et al, 1982), in patients with different fungal infections (Brass et al, 1982;Gascoigne et al, 1981) and in immunocompromised patients (Hann etal., 1982;Maksymiuk et al, 1982). In view of the dysmorphogenic effects of ketoconazole noted in animals (Heel et al, 1982) The poor vaginal absorption of ketoconazole may in part be due to the physicochemical properties of the drug.…”
Section: Introduction Methodsmentioning
confidence: 99%